SOSIAL MEDIA : Sarana Dakwah Di Era Digital - Yuli Eviyanti; Ricka Handayani; Romandiah Romandiah (J-MD Jurnal Manajemen Dakwah, 2024)
Abstract Social media has become an effective tool for spreading da'wah throughout the world. The aim of this research is to see how the use of social media can help da'wah in the digital era become more effective. The results show that the use of social media in da'wah has an important role and great potential. Da'wah messages can be spread quickly and effectively through social media, reaching a wider audience. However, preachers must use social media carefully and responsibly. Da'wah content must be correct, credible and relevant to Islamic teachings. It is very important for wise kiai, santri and social media users to work together. Challenges include not understanding social media etiquette and spreading misinformation. Ensuring data accuracy and improving digital literacy are examples of effective tactics and approaches. In da'wah, the use of social media has complex social effects, with benefits and negative effects that need to be considered. It is very important to understand and use social media correctly when using it for da'wah. Keywords: Social Media, Da'wah, Digital Era.